Arte Povera as a Tool in Critical Italian-Language Pedagogy - Formato, G. (International Journal of Linguistics, 2020)
Visual arts are culturally and historically significant to Italy and a reason why many people study the Italian language. This significance is visible in Italian-language classes, from mentions of high art in beginner-level textbooks to entire courses taught in advanced-level Italian devoted to these arts and their respective movements. The importance of these works to art history and to humanity at large cannot be denied relative to learning about Italian culture in the classroom. However, as presented in this literature review, it may be useful to reevaluate how these more traditional teaching subjects can be considered neutral, with a heavy emphasis on instruction as well as a subconscious perpetuation of racist, sexist, and capitalist ideals. By instead drawing upon the contemporary Italian Arte Povera movement a tool of critical pedagogy from beginner to advanced Italian-language courses, Italian art culture and language can be taught by using a more political, multidimensional approach focused on the learners’ contexts and histories. Thus, students may better understand themselves through Italian language and foster critical thinking, in addition to ultimately acquiring the language.